Nicotinic acetylcholine receptor signaling regulates inositol‐requiring enzyme 1α activation to protect β‐cells against terminal unfolded protein response under irremediable endoplasmic reticulum stress. Issue 4 (17th February 2020) - Ishibashi, Tatsuya; Morita, Shuhei; Kishimoto, Shohei; Uraki, Shinsuke; Takeshima, Ken; Furukawa, Yasushi; Inaba, Hidefumi; Ariyasu, Hiroyuki; Iwakura, Hiroshi; Furuta, Hiroto; Nishi, Masahiro; Papa, Feroz R; et al.
Abstract: Aims/Introduction: Under irremediable endoplasmic reticulum (ER) stress, hyperactivated inositol‐requiring enzyme 1α (IRE1α) triggers the terminal unfolded protein response (T‐UPR), causing crucial cell dysfunction and apoptosis. We hypothesized that nicotinic acetylcholine receptor (nAChR) signaling regulates IRE1α activation to protect β‐cells from the T‐UPR under ER stress. Materials and Methods: The effects of nicotine on IRE1α activation and key T‐UPR markers, thioredoxin‐interacting protein and insulin/proinsulin, were analyzed by real‐time polymerase chain reaction and western blotting in rat INS‐1 and human EndoC‐βH1 β‐cell lines. Doxycycline‐inducible IRE1α overexpression or ER stress agents were used to induce IRE1α activation. An α7 subunit‐specific nAChR agonist (PNU‐282987) and small interfering ribonucleic acid for α7 subunit‐specific nAChR were used to modulate nAChR signaling. Results: Nicotine inhibits the increase in thioredoxin‐interacting protein and the decrease in insulin 1/proinsulin expression levels induced by either forced IRE1α hyperactivation or ER stress agents. Nicotine attenuated X‐box‐binding protein‐1 messenger ribonucleic acid site‐specific splicing and IRE1α autophosphorylation induced by ER stress. Furthermore, PNU‐282987 attenuated T‐UPR induction by either forced IRE1α activation or ER stress agents. The effects of nicotine on attenuating thioredoxin‐interacting protein and preserving insulin 1 expression levels were attenuated by pharmacological and genetic inhibition of α7 nAChR. Finally, nicotine suppressed apoptosis induced by either forced IRE1α activation or ER stress agents. Conclusions: Our findings suggest that nAChR signaling regulates IRE1α activation to protect β‐cells from the T‐UPR and apoptosis under ER stress partly through α7 nAChR. Targeting nAChR signaling to inhibit the T‐UPR cascade may therefore hold therapeutic promise by thwarting β‐cell death in diabetes. Abstract : Nicotinic acetylcholine receptor signaling attenuated inositol‐requiring enzyme 1α signaling and Terminal Unfolded Protein Response (T‐UPR) under irremediable endoplasmic reticulum stress in rat INS‐1 and human EndoC‐βH1 β‐cell lines. The effects of nicotine on terminal unfolded protein response were reduced by pharmacological and genetic inhibition of nicotinic acetylcholine receptor α7 subunit. Finally, nicotine suppressed apoptosis induced by either forced inositol requiring enzyme 1α activation or endoplasmic reticulum stress.